2020
DOI: 10.1055/s-0040-1716750
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical Effects of Oral Thrombin and Factor Xa Inhibitors in Platelet Activation and Arterial Thrombosis

Abstract: Nonvitamin K oral anticoagulants (NOACs) or direct oral anticoagulants comprise inhibitors of factor Xa (rivaroxaban, apixaban, edoxaban) or factor IIa (dabigatran). Both classes efficiently interfere with the final or penultimate step of the coagulation cascade and showed superior net clinical benefit compared with vitamin K antagonists for prevention of thromboembolic events in patients with AF and for prevention and therapy of deep vein thrombosis and pulmonary embolism. None the less, accumulating data sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Interestingly, cessation of dabigatran may induce a state of platelet activation [ 167 ]. Those antiplatelet effects have also been proposed for the factor Xa inhibitors [ 168 ]. It should be stressed that conflicting results have been reported, with Arantes et al noting no differences in the platelet function of patients with coronary artery disease when treated with dabigatran [ 169 ].…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Interestingly, cessation of dabigatran may induce a state of platelet activation [ 167 ]. Those antiplatelet effects have also been proposed for the factor Xa inhibitors [ 168 ]. It should be stressed that conflicting results have been reported, with Arantes et al noting no differences in the platelet function of patients with coronary artery disease when treated with dabigatran [ 169 ].…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Polzin et al have reported that NOACs, in particular factor Xa inhibitors, can reduce NOX2-mediated ROS production. 41 Woźniak et al have demonstrated that rivaroxaban induces an indirect repair of DNA by inhibiting ROS production in a model of vascular endothelial damage with 25-hydroxycholesterol. 42 Treatment using apixaban and rivaroxaban that inhibit both direct and thrombin-mediated actions of FXa, in part mediated by activation of cellular proteaseactivated receptors, was associated with lower levels of 8-isoprostane as compared to dabigatran.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In 2020, we introduced optional “Visual Summaries” to convey the main message of the manuscript in a clear and concise graphic manner so that readers can grasp its contents and relevance at a glance. In the past two years, we have received an increasing number of such graphical abstracts which greatly improved the reading quality of the articles published 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 some of which have even been selected for the T&H Issue Cover 4 5 11 15 33 38 ( Fig. 2 ).…”
Section: What's New?mentioning
confidence: 99%